2019
DOI: 10.1111/tbed.13351
|View full text |Cite
|
Sign up to set email alerts
|

Different dynamics of Usutu virus infections in Austria and Hungary, 2017–2018

Abstract: Usutu virus (USUV), a mosquito‐borne flavivirus closely related to West Nile virus, emerged in Austria in 2001, when it caused a considerable mass‐mortality of Eurasian blackbirds. Cases in birds increased until 2003 and quickly declined thereafter, presumably due to developing herd immunity. Since 2006, no further cases were recorded, until two blackbirds were tested positive in 2016. In Hungary, USUV first appeared in 2005 and has caused only sporadic infections since then. Initially, the only genetic USUV l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 50 publications
(91 reference statements)
1
33
0
Order By: Relevance
“…It is important to note, that the infected birds in this study all died naturally, and it remains open, to what extent they suffered from concomitant diseases or other pathogens that might have favoured the severity of malaria infections. Birds of the family Turdidae, in particular Eurasian blackbirds, are highly susceptible to Usutu virus (USUV) infection, and epizootic USUV-associated bird mortalities have been reported from several European countries, including Austria [31,[44][45][46][47][48][49][50][51][52]. More recent studies reported high USUV and Plasmodium coinfection rates in Eurasian blackbirds, suggesting that coinfection increases the likeliness of mortalities in infected birds [24,44].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, that the infected birds in this study all died naturally, and it remains open, to what extent they suffered from concomitant diseases or other pathogens that might have favoured the severity of malaria infections. Birds of the family Turdidae, in particular Eurasian blackbirds, are highly susceptible to Usutu virus (USUV) infection, and epizootic USUV-associated bird mortalities have been reported from several European countries, including Austria [31,[44][45][46][47][48][49][50][51][52]. More recent studies reported high USUV and Plasmodium coinfection rates in Eurasian blackbirds, suggesting that coinfection increases the likeliness of mortalities in infected birds [24,44].…”
Section: Discussionmentioning
confidence: 99%
“…A passive surveillance regarding wild bird mortality cases was performed at the Veterinary Diagnostic Directorate of the National Food Chain Safety Office. Bird carcasses examined in the avian influenza monitoring scheme were also tested for Flavivirus infection as previously described [18]. Pathology, histology, and polymerase chain reaction (PCR) were performed, and partial WNV sequences were obtained from positive cases.…”
Section: Sample Collectionmentioning
confidence: 99%
“…However, it seems to be most often associated with Culex pipiens [ 22 , 29 , 38 , 39 , 40 ]. The main natural reservoir hosts of USUV are birds; the virus presence was demonstrated to date in 101 bird species belonging to 18 orders and 38 families [ 7 , 8 , 22 , 41 ]. However, the natural virulence spectrum of USUV seems rather limited, with a marked virulence in the European blackbird ( Turdus merula ) [ 42 ], house sparrow ( Passer domesticus ) [ 43 ], grey owl ( Strix nebulosa ) [ 44 ], and common scoter ( Melanitta nigra ) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%